THE METHODOLOGY OF PSYCHOLOGICAL EVALUATION OF PROFESSIONAL COMPETENCE OF IT SPECIALIST - AVANESYAN, HRANT; HOVSEPYAN, NAREK (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
The article is devoted to the study of the professional competence of an IT specialist and the assessment of human capital and the psychological capital. The approaches of both Armenian and foreign authors (Avanesyan, Lutans, Hodges, Chavush, Kapusuz, and others) were examined to study this problem. The content analysis method, which allows us to draw the following conclusion, is used in the article. The Managers, including IT companies’ managers, should focus on the human capital and psychological capital of their employees. Human capital creates an infrastructure for socio-economic development. The characteristics of human capital mainly affect organizational behavior and productivity. The results of the study show that psychological capital can be defined as a key factor in achieving goals, sustainable psychological well-being, and satisfaction both in life and at work.
Keywords: human capital, psychological capital, professional qualities, competence, human resources, staff selection, psychological assessment, specialists of IT sector